Aerosol transfer of bladder urothelial and smooth muscle cells onto demucosalized colonic segments for bladder augmentation: In vivo, long term, and functional pilot study. Issue 5 (October 2015) - Hidas, Guy; Lee, Hak J.; Bahoric, Andrej; Kelly, Maryellen S.; Watts, Blake; Liu, Zhongbo; Saharti, Samah; Lusch, Achim; Alamsahebpour, Alireza; Kerbl, David; Truong, Hung; Zi, Xiaolin; et al.
Summary: Background: Bladder augmentation technique has changed over the years and the current practice has significant adverse health effects and long-term sequelae. Previously, we reported a novel cell transfer technology for covering demucosalized colonic segments with bladder urothelium and smooth muscle cells through an aerosol spraying of these cells and a fibrin glue mixture. Objective: To determine the long-term durability and functional characteristics of demucosalized segments of colon repopulated with urothelial cells in the bladder of swine for use in augmentation cystoplasty. Study design: Nine swine were divided into three groups. The first group (control) underwent standard colocystoplasty; the second group underwent colocystoplasty with colonic demucosalization and aerosol application of fibrin glue and urothelial cell mixture; in the third group detrusor cells were added to the mixture described in group two. The animals were kept for 6 months. Absorptive and secretory function was assessed. Bladders were harvested for histological and immunohistochemical evaluation. Results: All animals but one in the experimental groups showed confluent urothelial coverage of the colonic segment in the bladder without any evidence of fibrosis, inflammation, or regrowth of colonic epithelial cells. Ten percent of the instilled water in the bladder was absorbed within an hour in the control group, but none in experimental groups( p  = 0.02). The total urine sediment and protein contents were higher in the control group compared with experimental groups ( p  < 0.05). Figure One animal in group three showed an extensive scar with sloughed urothelium, fibroblasts, and massive collagen deposition. Discussion: Both study groups developed a uniform urothelial lining. Histologically, the group with smooth muscle had an added layer of submucosal smooth muscle. Six months after bladder augmentation the new lining was durable. We were also able to demonstrate that the reconstituted augmented segments secrete and absorb significantly less than the control colocystoplasty group. We used a non-validated simple method to evaluate permeability of the new urothelial lining to water. To determine if the aerosol transfer of bladder cells would have behaved differently in the neurogenic bladder population, this experiment should have been performed in animals with neuropathic bladders. Conclusion: Aerosol spraying of single cell suspension of urothelial and muscular cells with fibrin glue resulted in coverage of the demucosalized intestinal segment with a uniform urothelial layer. This new lining segment was durable without regrowth of colonic mucosa after 6 months. The new reconstituted segment absorbs and secretes significantly less than control colocystoplasty.